2005
DOI: 10.1667/rr3421.1
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Responses at Low Radiation Doses

Abstract: Increased cell killing after exposure to low acute doses of X rays (0-0.5 Gy) has been demonstrated in cells of a number of human tumor cell lines. The mechanisms underlying this effect have been assumed to be related to a threshold dose above which DNA repair efficiency or fidelity increases. We have used cells of two radioresistant human tumor cell lines, one that shows increased sensitivity to low radiation doses (T98G) and one that does not (U373), to investigate the DNA damage response at low doses in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
58
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 43 publications
9
58
0
1
Order By: Relevance
“…This cell line is semipermissive for HCMV infection (40), as would be expected given our previous results showing that p53 plays an important role in HCMV replication (11). Despite their mutagenic profile, T98G cells are capable of mounting a DSB damage response (81). G 0 -arrested T98G cells infected at an MOI of 5 with BrdU-labeled HCMV displayed labeled HCMV genomes in approximately 90% of the cell nuclei by 6 h p.i.…”
Section: Resultssupporting
confidence: 58%
“…This cell line is semipermissive for HCMV infection (40), as would be expected given our previous results showing that p53 plays an important role in HCMV replication (11). Despite their mutagenic profile, T98G cells are capable of mounting a DSB damage response (81). G 0 -arrested T98G cells infected at an MOI of 5 with BrdU-labeled HCMV displayed labeled HCMV genomes in approximately 90% of the cell nuclei by 6 h p.i.…”
Section: Resultssupporting
confidence: 58%
“…In the autonomous pathways model, the DNA damagesignaling network activates DNA repair and cell death simultaneously and automatically, which is consistent with the current evidence [2,3,[7][8][9][10][11][12][13][14][15][16][17]. In this review, we will examine these two conceptual models for their capacity to explain DNA damage-induced cell death in the developing central nervous system (CNS) of rodents.…”
Section: Autonomous Pathwayssupporting
confidence: 65%
“…Generally speaking, cell death is a delayed response to DNA damage, resulting in elimination of the damaged cell ( Figure 1). The cell-protective and cell-destructive responses to DNA damage are downstream of a common signal transduction network that has been studied intensively in recent years ( Figure 1) (reviewed in Huen and Chen, in this issue) [2,3,[7][8][9][10][11][12][13][14][15][16][17]. While most protein components of this signaling network have been identified, the current knowledge does not explain when and why a damaged cell will choose to die.…”
Section: Introductionmentioning
confidence: 99%
“…These findings go in line with Short et al, who found that ATM-dependent signaling to downstream targets, such as TP53, CHK1 and CHK2, occurs even at low doses of 0.2 Gy IR. 35 In this regard, Suzuki et al 36 showed that the activated and phosphorylated ATM protein in the nucleus between doses of 10 mGy and 1 Gy is connected to multiple signal transduction pathways.…”
Section: Discussionmentioning
confidence: 99%